تطوير نظام خبير لاختبار نموذج المعالجة البيولوجية لمياه الصرف الصحي في سوريا - هناء سلمان- جمال عمران (Tishreen University, 2022)
تطوير نظام خبير لاختبار نموذج المعالجة البيولوجية لمياه الصرف الصحي في سوريا